Analysis Types Figurative Language in Maya Angelou's Poems - lestari, Mimin Ayu; Sogimin, Sogimin (LINGUAMEDIA Journal, 2024)
The use of figurative language adds to the unique of the literature, which can create an imaginative atmosphere for the reader. The analysis is about type’s figurative language of in Maya Angelou's. There are three poems the writer uses in thesis. The research method of this thesis is descriptive qualitative using a descriptive approach. The purpose of this analysis is to find figurative language in Maya Angelou's poem. The selected poems are "Still I Rise", "Caged Bird", and “Alone". The theory used in this research was the theory of figurative language by Gorys Keraf. In analyzing the data the writer analyzes figurative language found in the three poem and draws the final conclusion based on the results of the data analysis. In the analysis and discussion, it is found the meaning of the three poem by Maya Angelou. "Still I Rise" contains seven figurative language, i.e. symbol, simile, irony, repetition, personification, cynicism, metaphor. "Caged Bird" contains four types of figurative language, i.e. personification, metaphor, irony, symbol. "Alone" contains four types of figurative language, i.e. Personification, metaphor, symbol, repetition. The result of the analysis shows that there are many figurative language found in Maya Angelou's poem. Key words: Poetry, Figurative Language, Maya Angelou